Autonomy, workload, work-life balance, and job performance among teachers - Zati Iwani, Tjik @ Zulkarnain (2015)
The purpose of this research is to examine the relationship between autonomy, workload and work-life balance on job performance among secondary school teachers in Alor Setar, Kedah. A total of 302 teachers are participated in the study. Regression analyses were used to test the hypotheses. Based on the explanatory factor analysis result, the independent variables for autonomy are control over methods, control at work and control over timing, workload and Work Personal Life Enhancement (WPLE) and Work Interference with Personal Life (WIPL) for worklife balance while dependent variables are sportsmanship, task performance, courtesy, altruism and conscientiousness. The results showed that control over methods of autonomy was found to have a positive relationship with task performance, altruism and conscientiousness of job performance. Control at work reportedly has significant relationship with courtesy but negatively with sportsmanship of job performance while control over timing had significant but negative relation with sportsmanship, courtesy and conscientiousness. Moreover, it was found that workload also has a positive relationship with task performance and courtesy. Further, for work-life balance dimension, Work Interference with personal life (WIPL) found out to have significant but negative relationship with sportsmanship of job performance while Work Personal Life Enhancement (WPLE) have significant relationship with three out of five job performance dimension which is courtesy, altruism and conscientiousness. Limitations of the study, suggestions for future research, theoretical and practical implication were also highlighted